3D-Spiral Small Antenna Design and Realization for Biomedical Telemetry in the MICS band - A. K. Skrivervik; J. Abadia; F. Merli; J. Zurcher; J. R. Mosig (Radioengineering, 2009)
This work presents the design and realization procedure of small implantable antenna for biotelemetry applications. The radiator occupies a volume smaller than 3 cm3 (without its biocompatible insulation), is well matched within the Medical Implanted Communications System band and shows an adequate gain (-28.5 dB) while introduced in the appropriate equivalent body medium. The latter is a homogeneous phantom with muscle dielectric properties. A prototype has been manufactured and measurements agree with theoretical predictions. Particular attention is paid to the building requirements such as the presence of glue. Speciﬁc Absorption Rate (SAR) distribution has been computed evaluating the maximum power deliverable to the antenna in order to respect the regulated SAR limitation.